Blood collection from dairy calves at exsanguination post-slaughter yields similar biochemical and packed cell volume measurements compared with in vivo collection during lairage. (June 2020) - Roadknight, Natalie; Courtman, Natalie; Mansell, Peter; Jongman, Ellen; Clarke-Errey, Sandy; Fisher, Andrew
Abstract: Blood collection at exsanguination is a method of collecting samples at abattoirs which itself has no effect on animal welfare, compared with collection prior to stunning. However, there is the potential for artefact to affect measurements. It was hypothesised that, for most blood analytes measured, the differences between lairage and exsanguination measurements would be minimal, except for creatine kinase, which was expected be higher in exsanguination samples. Fifty-nine male dairy calves approximately 5–10 days old were sampled prior to slaughter, and again during exsanguination after stunning. Each sample was analysed for packed cell volume, serum urea, beta-hydroxybutyrate, gamma-glutamyl transferase, total protein, glucose and creatine kinase concentrations. Exsanguination and lairage blood results were compared using a paired t -test. There were no significant differences between the measurements taken at exsanguination compared with lairage for packed cell volume, urea and beta-hydroxybutyrate. Glucose concentrations were higher in exsanguination samples, and total protein concentrations were lower, but for both of these analytes the differences were clinically small. Gamma-glutamyl transferase activity was lower in exsanguination samples compared with lairage samples. Creatine kinase activity was higher in exsanguination samples. It was concluded that collecting blood at exsanguination is a valid method for collecting samples for measurement of packed cell volume, urea, and beta-hydroxybutyrate in calves. Glucose and total protein can also yield useful measurements in these samples, though care needs to be taken with interpretation given the minor differences between exsanguination and lairage measurements. Exsanguination samples may be unsuitable for creatine kinase and gamma-glutamyl transferase measurement. Highlights: Abattoir blood collection at exsanguination does not further impact animal welfare. Exsanguination method suitable for packed cell volume, urea, beta-hydroxybutyrate. Minor differences in glucose and total protein compared with lairage samples. Exsanguination samples may be unsuitable for measuring gamma-glutamyl transferase. Exsanguination samples may also be unsuitable for measuring creatine kinase.